Chaetomitrium Lancifolium - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are rather laxly branched; filamentous propagules are abundant in leaf axils of branches; (2) stem leaves are often undulate at upper one-third; (3) branch leaves are flattened (some are divergent), and strongly constricted below apices; (4) leaf margins are distinctly and regularly denticulate to the base with deeply trifid or multifid teeth; (5) lamina cells are strongly prorate to spiculose-prorate and thick-walled; (6) inner perichaetial leaves are similar to stem leaves in length; (7) setae are 4.5-5.5 mm long, and densely papillose but smooth at the extreme base.